Patient level barriers to accessing TB care services during the COVID-19 pandemic in Uganda, a mixed methods study - Mudarshiru Bbuye; Stella Zawedde Muyanja; Isaac Sekitoleko; Roma Padalkar; Nicole Robertson; Madeline Helwig; Dennis Hopkinson; Trishul Siddharthan; Peter Jackson (BMC, 2024)
Abstract Introduction Lockdown measure has been utilized widely to mitigate COVID-19 pandemic transmission and recently during the 2022 Sudan Ebola Virus Disease outbreak in Uganda. These have setback effects on the continuity of essential health services such as tuberculosis (TB) care, reversing progress made in the fight against tuberculosis (TB) over the past decade. We set out to understand patient-reported barriers to accessing TB care services during the COVID-19 pandemic in Uganda. Methods Mixed methods study involving review of medical records of TB patients who received TB care from January to September 2020. We used quantitative and qualitative methods including phone questionnaires and in-depth interviews. We carried out descriptive statistics, a chi-square test and conducted a thematic analysis. Results We carried out phone interviews with 672 participants. The majority (60%) were male and with an average of 35 years (SD:11). A significantly higher proportion of patients reported a barrier to TB care access during the COVID-19 lockdown than pre-lockdown (79.9% vs. 68.1% p = 0.027). We carried out in-depth interviews with 28 participants (54% (15/28): male). Barriers experienced by these participants included lack of a means of transport to reach the health facility, lack of money to pay the transport fares, long distances to the facility, fear of COVID-19 infection, stigma due to overlap between TB and COVID-19 symptoms, and few health care workers available during the lockdown period. Conclusion Lockdown measures instituted to mitigate the transmission of COVID1-19 affected access to TB care services in Uganda. Uganda is at risk of future emerging and re-emerging diseases of epidemic potential. Therefore, there should be measures to ensure the continuity of essential services such as tuberculosis care during the implementation of future epidemic response interventions such as a lockdown.